Sustained Drug Release From Liposomes for the Remodeling of Systemic Immune Homeostasis and the Tumor Microenvironment - Zheng, Anjie; Xie, Fang; Shi, Sanyuan; Liu, Shounan; Long, Jinfeng; Xu, Yuhong (Frontiers in Immunology, 2022)
Myeloid Derived Suppressor Cells (MDSCs) play important roles in constituting the immune suppressive environment promoting cancer development and progression. They are consisted of a heterogeneous population of immature myeloid cells including polymorphonuclear MDSC (PMN-MDSC) and monocytes MDSC (M- MDSC) that are found in both the peripheral and in the tumor microenvironment (TME). While previous studies had shown that all-trans retinoic acid (ATRA) could induce MDSC differentiation and maturation, the very poor solubility and fast metabolism of the drug limited its applications as an immune-modulator for cancer immunotherapy. We aimed in this study to develop a drug encapsulated liposome formulation L-ATRA with sustained release properties and examined the immuno- modulation effects. We showed that the actively loaded L-ATRA achieved stable encapsulation and enabled controlled drug release and accumulation in the tumor tissues. In vivo administration of L-ATRA promoted the remodeling of the systemic immune homeostasis as well as the tumor microenvironment. They were found to promote MDSCs maturation into DCs and facilitate immune responses against cancer cells. When used as a single agent treatment, L-ATRA deterred tumor growth, but only in immune-competent mice. In mice with impaired immune functions, L-ATRA at the same dose was not effective. When combined with checkpoint inhibitory agents, L-ATRA resulted in greater anti-cancer activities. Thus, L-ATRA may present a new IO strategy targeting the MDSCs that needs be further explored for improving the immunotherapy efficacy in cancer.